Study of Antibiotic Sensitivity of Pathogenic and Vaccine Strains of Brucella - Mamatova , Zamira; Achilov , Odil; Khudjamshukurov , Adkham; Yuldasheva, Farangiz (American Journal of Bioscience and Clinical Integrity, 2025)
Antibiotic resistance of infectious disease pathogens to antibiotics prescribed to combat them is a pressing issue for researchers – microbiologists in terms of determining the correct treatment protocol for many human and animal infections. Irrational use of antibiotics leads to the emergence of new mutated strains or antibiotic-resistant pathogens. This article presents the results of a comparative analysis of antibiotic sensitivity of pathogenic Br. abortus 99 and vaccine Br. abortus 19 strains of Brucella to 15 antibiotics of various origins. This article presents the results of a comparative analysis of the antibiotic sensitivity of pathogenic Br. abortus 99 and vaccine Br. abortus 19 strains of Brucella to 15 antibiotics of various origins. It was established that the vaccine Br. abortus 19 and pathogenic Br. abortus 99 strains of Brucella, which are not exposed to environmental factors, factors of the body’s immune system and the surrounding microbiological biotome of the body, exhibit sensitivity to all antibiotics used in the experiment, and also that the vaccine strain Br. abortus 19 demonstrates greater sensitivity to the 6 antibiotics used in the experiment (rifampicin, ciprofloxacin, sisomycin, ofloxacin, ceftriaxone, azithromycin) out of 15 than the pathogenic strain Br. abortus 99.